Pesan Moral Ayat Isjudū li Ādama dalam Q.S al-Baqarah: 34 dan Q.S. al-Kahfi: 50 (Studi Komparasi Tafsir al-Mishbah dan Tafsir al-Azhar) - Muhammad Faishal Haq (LP2M UIN Sunan Kalijaga, 2021)
This paper aims to reveal what is the true moral message in the sentence Isjudu> li A>dama. Therefore, the research focuses on the fragments of these verses in Surah al-Baqarah verse 34 and al-Kahfi verse 50. Understanding the moral message in every verse of the Koran is very important to know. It aims to make the message of the Koran relevant today. In this study, the analysis was carried out on two tafsir works, namely Tafsir Al-Mishbah by M. Quraish Shihab and Tafsir Al-Azhar by Hamka. Both are products of Indonesian interpretation, they use the tahlily method of interpretation, with the pattern of adabi ijtima'i. However, from the results of the author's analysis using qualitative research methods and literature, and supported by comparative studies with several aspects of the object of study, the conclusion is that the interpretation in the Al-Misbah Tafsir; specifically on the two verses above, it is more comprehensive than the explanation of the Tafsir Al-Azhar. And also, in the Tafsir Al-Misbah, a more dominant moral message is found, in addition to mutual respect, respect and respect as fellow beings, Al-Baqarah verse 34 can be the basis for the obligation to respect those who are knowledgeable. [Tulisan ini bertujuan untuk mengungkap apa sebenarnya pesan moral pada kalimat Isjudu> li A>dama. Maka dari itu, penelitian terfokuskan pada penggalan ayat tersebut yang ada dalam surat al-Baqarah ayat 34 dan al-Kahfi ayat 50. Memahami pesan moral dalam setiap ayat al-Quran sangat penting untuk diketahui. Hal tersebut bertujuan untuk merelevansikan pesan al-Quran di zaman sekarang. Dalam penelitian ini, analisis dilakukan pada dua karya tafsir, yakni Tafsir Al-Mishbah karya dari M. Quraish Shihab dan Tafsir Al-Azhar karya dari Hamka. Keduanya merupakan produk tafsir nusantara, sama sama menggunakan metode tafsir tahlily, bercorak adabi ijtima‘i. Namun dari hasil analisis penulis menggunakan metode penelitian kualitatif dan kepustakaan, serta ditunjang dengan studi komparasi/muqaran dengan beberapa aspek obyek kajian dihasilkan kesimpulan bahwa tafsiran dalam Tafsir Al-Misbah; khusus pada dua ayat di atas, lebih komprehensif dibandingkan penjelasan Tafsir Al-Azhar. Dan juga, dalam Tafsir Al-Misbah ditemukan pesan moral yang lebih dominan, selain harus saling memuliakan, menghormati dan menghargai sebagai sesama makhluk, Al-Baqarah ayat 34 dapat menjadi dasar tentang kewajiban menghormati orang-orang yang berpengetahuan.]",